The Cloud is the Router: Enabling Bandwidth-Efficient and Privacy-Aware Mobile Applications with Contrail - Stuedi, Patrick; Mohomed, Iqbal; Balakrishnan, Mahesh; Ramasubramanian, Rama; Mao, Z. Morley; Wobber, Ted (Microsoft Research, 2010)
Collaborative applications running on 3G devices often rely on cloud-based servers for computation and storage. A peer-to- peer approach to building these applications can provide benefits such as enhanced privacy and bandwidth efficiency. We propose Contrail, an asynchronous network architecture that uses the cloud to relay messages between 3G devices. Contrail employs selective receiver-specific filters at sending devices to ensure that only relevant data consumes precious bandwidth. Our framework offers pull-based communications primitives suitable for mobile devices that are often either inactive or subject to poor network connectivity. Contrail enables robust mobile applications without making assumptions about the security of individual cloud providers. We have implemented Contrail within Windows Azure and demonstrate several sample applications executing across Windows Mobile devices.